Satire, modernity, transculturality in late nineteenth and early twentieth century North India - Kumar, Prabhat (2018)
Stichwörter: Trancscuturality, Modernity, Colonialism, Tradition, History, Language, Literature, India, Literary Culture, Visual Culture, Cartoon, Print Culture, Public Sphere, Hindi Vyangya Sahitya, Vyangya-Chitra; Punch, Matvala, Chand, Pratap, Hindu Panch, Sudha, Madhuri, Ganga, Bharatendu Harishchandra, Radhacharan Goswami, Pratap Narayan Mishra, Ramavatar Sharma, J P Shrivastava, Mahavir Prasad Dvivedi, Ramchandra Shukla, Banarasidas Chaturvedi, Shivpujan Sahay, Mohanlal Mahto 'Viyogi'